MALFORMATION IN THE BILL OF A GREEN KINGFISHER (CHLOROCERYLEAMERICANA) IN PRE–DELTA NATIONAL PARK, DIAMANTE, ENTRE RIOS (ARGENTINA) (Natura Neotropicalis, 2018)
Malformations of bird bills have been reported for various bird families and may result from several factors. We document an individual of Green Kingfisher Chloroceryle americana in Pre–Delta National Park, province of Entre Ríos (Argentina), with important malformations along its upper mandible and at the bases of both mandibles. We discuss the low frequency worldwide of reports of bill malformations in kingfishers (Alcedinidae).
Keywords: malformations; upper mandible; Alcedinidae